Experimental and computational interaction studies of terbium (III) and lanthanide (III) complexes containing 2, 2′-bipyridine with bovine serum albumin and their in vitro anticancer and antimicrobial activities. Issue 14 (22nd September 2021) - Aramesh-Boroujeni, Zahra; Aramesh, Nahal; Jahani, Shohreh; Khorasani-Motlagh, Mozhgan; Kerman, Kagan; Noroozifar, Meissam
Abstract: To investigate the chemotherapeutic and pharmacokinetic aspects of two lanthanide complexes (Tb(III) and La(III) containing 2, 2′-bipyridine ligand), in vitro binding studies were carried out with BSA by employing multiple biophysical methods and molecular modeling study. There are different techniques containing fluorescence, absorption spectroscopy and competitive experiments to determine the interaction mode between BSA and these complexes. These complexes efficiently quenched the BSA emission through a static procedure. The results showed that the terbium and lanthanum complexes exhibited a high propensity for BSA interaction via van der Waals force. Further, competitive examination and docking study showed that the interaction site of these complexes on BSA is site III. The results of docking calculations were in good agreement with experimental examinations. Also, the energy transfer from BSA to these complexes has happened with high possibility. Moreover, antimicrobial studies of different bacterial and fungi indicated its promising antibacterial activity. In vitro cytotoxicity of the Tb complex and La complex was carried out in MCF-7 and A-549 cell lines, which revealed significantly good activity. Communicated by Ramaswamy H. Sarma